Chronology of the Radiographic Appearances of the Calcium Sulfate-Calcium Phosphate Synthetic Bone Graft Composite following Resection of Bone Tumors: A Follow-up Study of Postoperative Appearances. Issue 1 (February 2016) - Tan, Victoria; Evaniew, Nathan; Finlay, Karen; Jurriaans, Erik; Ghert, Michelle; Deheshi, Benjamin; Parasu, Naveen
Purpose: The objective of the study was to characterize the radiographic appearance of graft resorption and new bone incorporation into a postresection defect of the calcium-sulfate calcium-phosphate synthetic bone graft composite following resection of benign bone tumours. Methods: Twenty-five patients who underwent treatment with the CaSO4 /CaPO4 synthetic graft following bone tumour resection were retrospectively identified from our oncology database. Postoperative radiographs were assessed for: 1) combined partial graft resorption and ingrowth at the graft site; 2) complete graft resorption with complete incorporation of new bone into the defect. After chronologically grouping radiographs, the volume of graft material used to fill bony defects, radiographic evidence of complications, and patterns of resorption were recorded. Results: Partial resorption of graft material/partial ingrowth of new bone was seen in 21 patients at 2.5 months postoperatively. Complete resorption of graft with complete new bone incorporation at the graft site was seen in 94% of cases (15 of 16) by 10 months after surgery. Mean time to complete incorporation of new bone was 6.7 months. Time to resorption of the graft with new bone ingrowth was found to be related to the volume of graft used with smaller volumes showing earlier resorption. For all cases demonstrating resorption (21 of 21), the pattern observed was peripheral to central. Five patients developed complications, including tumour recurrence, cyst formation, and graft site infection. Conclusion: Our study suggests a characteristic time and volume related radiographic pattern of resorption and new bone ingrowth with the CaSO4 /CaPO4 synthetic graft. Findings that deviate from this pattern may represent complication and warrant additional follow-up.